Visualization of DNA Replication in Single Chromosome by Stable Isotope Labeling - Nagata, Kosuke; Bajo, Ken-ichi; Mitomo, Hideyuki; Fujita, Ryosuke; Uehara, Ryota; Ijiro, Kuniharu; Yurimoto, Hisayoshi (Cell Structure and Function, 2021)
Among the inheritance of cellular components during cell division, deoxyribonucleic acid (DNA) and its condensate (chromosome) are conventionally visualized using chemical tag-labeled nucleotide analogs. However, associated mutagenesis with nucleotide analogs in the visualization of chromosomes is cause for concern. This study investigated the efficiency of using stable isotope labels in visualizing the replicating cultured human cell-chromosomes, in the absence of analog labels, at a high spatial resolution of 100 nm. The distinct carbon isotope ratio between sister chromatids reflected the semi-conservative replication of individual DNA strands through cell cycles and suggested the renewal of histone molecules in daughter chromosomes. Thus, this study provides a new, powerful approach to trace and visualize cellular components with stable isotope labeling.Key words: stable isotope, chromosome replication, semi-conservative replication, imaging, mass spectrometry